Reversible photochromic energy storage polyurea microcapsules via in-situ polymerization. (15th March 2021) - Sun, Shaofeng; Gao, Yan; Han, Na; Zhang, XingXiang; Li, Wei
Abstract: In this study, reversible photochromic polyurea (PU) microcapsules had been innovatively designed and prepared by in-situ polymerization successfully, which exhibited good latent heat storage and release properties. For the microcapsules, butyl stearate containing photochromic dye (spirooxazine) was used as the core material and PU as the shell material. The surface morphology, melt crystallization, thermal cycling durability, thermal stability and mechanical properties of PU microcapsules were systematically investigated with field emission scanning electron microscope (FE-SEM), different scanning calorimetry (DSC), thermogravimetric (TG) and dynamic mechanical analysis (DMA). And the light-to-thermal conversion performance was studied under sun simulation system. The results showed that the microcapsules synthesized with F2850, a new lipophilic amine, had better morphologies and uniform particle size distribution. When the mass ratio of isophorone diisocyanate (IPDI) to F2850 was 1:2, the surface of the microcapsules was smooth and compact thus resulting in the microcapsules with the highest mechanical strength. In addition, the PU microcapsules exhibited high energy storage efficiency, excellent thermal stability and thermal cyclic durability. Finally, the reversible photochromic microcapsules also presented prominent light-to-thermal conversion properties. What's more, the temperature of the reversible photochromic microcapsules was nearly 4.9 °C higher than that of microcapsules at the same irradiation time. Graphical abstract: Image 1 Highlights: The microcapsules synthesized with a new lipophilic amine of F2850. Microcapsules were prepared by simple and high-efficiency in-situ polymerization. The photochromic microcapsules presented light-to-thermal conversion properties.